2003
DOI: 10.1007/s00436-002-0694-4
|View full text |Cite
|
Sign up to set email alerts
|

Purification and localization of a 10 kDa calcareous corpuscle binding protein of Spirometra mansoni plerocercoid

Abstract: In cestode parasites, calcareous corpuscles are thought to be associated with a number of intracellular physiologies by regulating the trafficking of mineral components. We previously separated these particular components by Ficoll, and their binding proteins of 10 kDa and 35 kDa in the Spirometra mansoni plerocercoid (sparganum). In the present study, we purified a 10 kDa protein employing octyl-Sepharose CL-4B affinity chromatography. Anti-serum raised against the purified protein showed specific reactions t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Most of these ligands shared common properties of calcium dependency [ 35 37 ] and/or post-translationally modified by glycosylation [ 8 ]. Previous studies have reported that cestode CC bound to calcium binding proteins [ 20 , 23 ] and glycoproteins [ 21 , 23 ]. Calcium-related biochemical properties of TsMFas1 and TsMFas2 proteins were not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…Most of these ligands shared common properties of calcium dependency [ 35 37 ] and/or post-translationally modified by glycosylation [ 8 ]. Previous studies have reported that cestode CC bound to calcium binding proteins [ 20 , 23 ] and glycoproteins [ 21 , 23 ]. Calcium-related biochemical properties of TsMFas1 and TsMFas2 proteins were not examined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown for other species that, aside from the various functions ascribed to calcareous corpuscles, e.g. osmoregulation and protection from abnormal calcification (28), these structures have the capacity of binding proteins (29,30). Whether they behave as a reservoir for EgA31 cannot be decided with the present observations.…”
Section: Discussionmentioning
confidence: 99%
“…Formation of CC has been proposed as a mechanism for protecting cysticerci from calcification [79]. The CC represent about 10% of the dry weight of total larval tissue [82]. It has been estimated that in aged T. s o l i u m cysticerci, calcareous corpuscles can represent up to 41% of the dry weight [81,82].…”
Section: The Calcareous Corpuscles As a Final Deposit For Host Proteinsmentioning
confidence: 99%